Optimización de la productividad en la linea Pet Mesal en la empresa Fuentes San Felipe S.A. - Soledispa Pazmiño, Johanna Valeria (2023)
The company Fuentes San Felipe, located in the city of Latacunga, specifically in the San Felipe neighborhood, is dedicated to the bottling and marketing of mineral water with and without gas, as well as gaseous beverages of different flavors. This company is characterized by its strategic location, as it has its own sources of mineral water, which in turn is purified for the processes in the company's production. The company is in constant growth, so it is seen in the need to solve problems that affect productivity; one of these is the delay in time in the format changes in the machines, which causes production to decline and with this also economic revenues. For this reason, the present research project aims to optimize the productivity of the PET line “MESAL” in the company Fuentes San Felipe by focusing the study on the change of line for the production of its different presentations. A survey of machine operators was conducted to find out the main problem at the time of switching lines. Through observation and reasoning, data was collected directly in the work area, i.e., in the Mesal Line, to then sort and analyze the data. This project contains process diagrams, a method study, and the use of the SMED tool. It should be stressed that the project was carried out on two of the machines that take the most time to modify: the positioner and the Packing Machine. As a result of the research project, the time that was reduced in the format change process for the Positioner is 34 minutes and 19 seconds, and for the packager it is 9 minutes and 59 seconds. Increasing productivity by 9%.